The effects of antibiotics and antifungals added to plant culture media of “Triticosecale wittmarck" - COSMA, Anca Dana; PETRUȘ-VANCEA, Adriana (Studia Universitatis Babeș-Bolyai Biologia, 2017)
The experiment aimed to study the antibiotics or antifungals effect to prevent the infection in Triticosecale wittmarck micropropagation, without affecting the inoculum. After identifying the pathogens, which are frequently affecting the in vitro culture media, respectively Clostridium sp. and Cladosporium sp., we made the antibiogram and antifungal susceptibility testing. Among antibiotics and antifungals, to which one of them were found to be sensitive, we chose to add the following to the culture media: V1-gentamicin (GEN) - 40 mg/L, V2-tetracycline (TET) - 10 mg/L, V3- ciprofloxacin (CIP) - 40 mg/L, V4- clotrimazole (CLO) - 50 mg/L, V5-fluconazole (FLU) - 50 mg/L, V6-terbinafine (TER) - 25 mg/L, having the culture medium, without anti-contaminants additions, as control lot. At the end of the experiment we concluded that anti-contaminants, used in concentrations recommended by literature, have prevented infections, but reduced the capacity for germination rate of triticale. Just terbinafine can be added in triticale culture media, but it is necessary to study other lower concentration that does not affect the growing of inoculum.